Postexposure Prophylaxis against Anthrax: Evaluation of Various Treatment Regimens in Intranasally Infected Guinea Pigs - Altboum, Zeev (American Society for Microbiology, 2002)
The efficiency of postexposure prophylaxis against Bacillus anthracis infection was tested in guinea pigs infected intranasally with either Vollum or strain ATCC 6605 spores (75 times the 50% lethal dose [LD(50)] and 87 times LD(50,) respectively). Starting 24 h postinfection, animals were treated three times per day for 14 days with ciprofloxacin, tetracycline, erythromycin, cefazolin, and trimethoprim-sulfamethoxazole (TMP-SMX). Administration of cefazolin and TMP-SMX failed to protect the animals, while ciprofloxacin, tetracycline, and erythromycin prevented death. Upon cessation of treatment all erythromycin-treated animals died; of the tetracycline-treated animals, two of eight infected with Vollum and one of nine infected with ATCC 6605 survived; and of the ciprofloxacin group injected with either 10 or 20 mg/kg of body weight, five of nine and five of five animals, respectively, survived. To test the added value of extending the treatment period, Vollum-infected (46 times the LD(50)) animals were treated for 30 days with ciprofloxacin or tetracycline, resulting in protection of eight of nine and nine of nine animals, respectively. Once treatment was discontinued, only four of eight and five of nine animals, respectively, survived. Following rechallenge (intramuscularly) of the survivors with 30 times the LD(50) of Vollum spores, all ciprofloxacin-treated animals were protected while none of the tetracycline-treated animals survived. In an attempt to confer protective immunity lasting beyond the termination of antibiotic administration, Vollum-infected animals were immunized with a protective antigen (PA)-based vaccine concurrently with treatment with either ciprofloxacin or tetracycline. The combined treatment protected eight of eight and nine of nine animals. Following cessation of antibiotic administration seven of eight and eight of eight animals survived, of which six of seven and eight of eight resisted rechallenge. These results indicate that a combined treatment of antibiotics together with a PA-based vaccine could provide long-term protection to prevent reoccurrence of anthrax disease.